Mécanismes de transport, d'agrégation et de production du krill (Thysanoessa raschii et Meganyctiphanes norvegica) dans l'estuaire et le golfe du Saint-Laurent - Benkort, Deborah (Université Laval, 2019)
Krill are macrozooplanktonic crustaceans play a key role in the pelagic marine ecosystem. They represent a crucial trophic platform between planktonic primary producers and the upper food-web levels. In a context of environmental changes, understanding the impacts of the natural variability of physical forcing on krill physiology and population dynamics appears essential to better apprehend the dynamics, evolution and management of subarctic marine ecosystems. In the Estuary and Gulf of St. Lawrence (EGSL), krill communities are dominated by two sympatric species, names Meganyctiphanes norvegica and Thysanoessa raschii. The main objective of this research project was to study, through the development of biophysical models, the effects of environmental variability on the distribution, reproduction and growth of these two species. The project allowed us i) to build a species-specific physiological based model (IBM) for adult stage of both krill species and to validate it with available data; ii) to identify spatio-temporally the potential growth and reproduction areas in the EGSL for both species iii) to study the role of the intraspecific variability on T. raschii population dynamics facing the environmental variability. In the first chapter we built a physiological species-specific based model representing realistically the annual adult life cycle for both dominant species at the Rimouski station located in the St. Lawrence River Estuary. We showed that the production dynamics of M. norvegica and T. raschii individuals were strongly linked to the feeding environment. However, both species exhibited well different growth and reproductive trajectories, T. raschii showing a summer production season, while M. norvegica an autumnal production season. The model highlighted how understanding and implementing feeding processes was essential for accurate representation of the growth dynamics of each species. In the second chapter, we coupled the physiological model developed in Chapter 2 with a 3D general circulation ...